(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Factors Affecting Fruit Traders Income at Badung Market Denpasar City. Badung Market is one of the largest fruit trading centers in Denpasar City. The problem of decreasing demand for fruit and competition between fruit traders at Badung Market can affect traders’ income. The aim of this research is to analyze the characteristics of fruit traders and analyze the factors that influence the income of fruit traders at Badung Market. The sample for this research was 31 respondents using the Slovin formula. The method used is descriptive qualitative and quantitative with SPSS-26 analysis technique. The research results show that the dominant characteristics of traders are between the ages of 15-65 years, female, with a family dependent of between 0-3 people and are dominated by traders from the Denpasar area. Capital factors and length of business have a positive and significant effect on fruit traders’ income. Working hours have a negative and insignificant effect on fruit traders’ income. Business location has a positive and insignificant effect on fruit traders’ income. The determination test (R2) shows that 52% of the variation in the value of the dependent variable can be explained by the independent variable. Suggestions that can be given to fruit traders at Badung Market that fruit traders are expected to be able to increase their sales results by paying attention to factors such as increasing capital and increasing regular customers or business relationships.